2019
DOI: 10.1186/s41687-019-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the measurement properties of patient reported outcome measures used for adults with an ankle fracture

Abstract: BackgroundAnkle fractures are painful and debilitating injuries that pose a significant burden to society and healthcare systems. Patient reported outcome measures (PROMs) are commonly used outcome measures in clinical trials of interventions for ankle fracture but there is little evidence on their validity and reliability. This systematic review aims to identify and appraise evidence for the measurement properties of ankle specific PROMs used in adults with an ankle fracture using Consensus Based Standards fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…This questionnaire was developed in 1984 to evaluate patients’ function with ankle fractures [ 15 ]. A recent systematic review assessing patient-reported outcome measures used for adults with an ankle fracture found that OMAS has sufficient levels of reliability, internal consistency and construct validity [ 22 ]. The Short Form (SF-36) Survey is the most widely used health-related quality of life measure in research to date because of its history, reliability and validity [ 23 , 24 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…This questionnaire was developed in 1984 to evaluate patients’ function with ankle fractures [ 15 ]. A recent systematic review assessing patient-reported outcome measures used for adults with an ankle fracture found that OMAS has sufficient levels of reliability, internal consistency and construct validity [ 22 ]. The Short Form (SF-36) Survey is the most widely used health-related quality of life measure in research to date because of its history, reliability and validity [ 23 , 24 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…In Corney et al's study carried out with 243 patients applied to psychiatry clinic, Folate levels in the blood was screened and it was observed that deficiency in Folate levels was higher in endogen (29%) and neurotic (11%) depression [23].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in the literature have shown that low Folate level decreases the response to the treatment with antidepressant. One of those studies concluded that 45% of patients with normal Folate level responded to the treatment while it was only 7% in those with low Folate level [23].…”
Section: Discussionmentioning
confidence: 99%
“…In advance of the meeting, we will identify available guidance or existing consensus on how best to measure short-listed outcome domains. Where there is no existing consensus for potential outcome measures, the core research team will review key evidence sources to determine measurement quality [ 66 ], acceptability, and feasibility.…”
Section: Methodsmentioning
confidence: 99%